The Number of Patients with Acute Myocardial Infarction Decreased and Door-to-Balloon Time Delayed in COVID-19. (26th March 2021) - Ma, Tianyi; Huang, Yuli; Li, Wensheng; Zhong, Jianghua; Yang, Hui; Zhou, Yilei; Li, Meijun; Zhong, Wenhao; Cao, Yue; Lu, Shijuan; Hu, Yunzhao
Abstract : Background . At present, COVID-19 is sweeping the world, and all countries are actively responding. During the COVID-19 epidemic, the treatment of patients with acute myocardial infarction (AMI) may be affected. Methods . We reviewed data of patients with AMI from January 23 to April 23, 2020 (2020), and January 23 to April 23, 2019 (2019), who were admitted to two hospitals from Southern China. We collected clinical characteristics, comorbidities, treatment, prognosis, and key time segments to analyze. Results . The total number of patients that had been diagnosed with AMI in the two hospitals was 218 in 2020 and 260 in 2019. The number of AMI patients that were admitted to hospitals per day decreased in 2020. The percentage of patients with AMI who refused hospitalization in 2020 was significantly higher than that in 2019 (5.0% vs 1.5%, p = 0.028 ). There is no statistical difference in symptoms of the first medical contact (S2FMC) time between 2020 and 2019 (p = 0.552 ). Door-to-balloon (D2B) time of ST-elevation myocardial infarction (STEMI) patients who were treated with a primary percutaneous coronary intervention (pPCI) in 2020 was 79 (63.75–105.25) mins, while D2B time in 2019 was 57.5 (41.5–76.5) mins, which was statistically different from the two groups. Conclusions . COVID-19 had an impact on the number of AMI patients who were admitted to hospitals and the time of treatment. During the COVID-19 epidemic, the number of AMI patients that were admitted to hospitals per day was decreased, while the percentage of AMI patients that refused therapy in these two hospitals increased, and the D2B time of STEMI patients was also delayed.